Critical Phenomenology : The Essence of @Tarabasro Instagram Followers Experience about Beauty Standards - Vira Amalia Riansyah; Sunarto Sunarto; Nurul Hasfi (Interaksi Online, 2023)
This research aims to find the essence of @tarabasro instagram followers' experience about beauty standards using a critical phenomenology approach. Beauty standards are one of the social issues that are happening in today’s society and have impacted many women. In Indonesia, beauty standards have been constructed since the colonial era and the understanding of beauty in Indonesia still looked up to the western standards. The method used in this research is using a qualitative approach using Clark Moustakas theoretical underpinnings of phenomenology to assist a step-by-step process of conducting a phenomenological study with the object of women who follow Tara Basro between the age of 18 to 34 years old. The primary data used through an in-depth interview from four informants and relevant journals. The key findings of this research is that the informants are experiencing the negative effect of beauty standards in Indonesia, resulting in body dysmorphia, eating disorders and lack of self- acceptance. After finding Tara Basro's Instagram page the informants have a new perspective in how they see beauty standards which inspires them to love herself and embrace their natural appearance without having to meet beauty standards in Indonesia and thus in Indonesia it need more representation from actresses or influencer who have big following to not pushing the agenda of beauty standards rather that to spread the awareness of the importance to love their body without limits.